Intumescent fireproof coating for steel structure and preparation method of intumescent fireproof coating
By improving the proportion and process of adhesive and filler, an expanded steel structure fire-resistance coating with a porous carbon layer was prepared, which solved the problem of insufficient fire resistance of steel structures in fire, significantly delayed temperature growth and improved fire resistance.
Patent Information
- Application Number
- CN202411104436.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The mechanical properties of steel structures have sharply declined in fire or high temperatures, resulting in building collapse. The fire resistance of existing expansion fire-resistant coatings is insufficient and cannot effectively protect the steel structure.
Using epoxy ester modified aqueous acrylic acid, polyvinyl alcohol, and urea as binders, hydroxylated titanium dioxide composite glass hollow microbeads, porous ceramic powder, and inorganic mineral powder as fillers, combined with the carbon, nitrogen and phosphorus expansion system, improve the binder The proportion and process of fillers are used to prepare the expanded steel structure fire-retardant coating to form a porous carbon layer to improve the flame retardant performance.
It significantly improves the fire resistance of expanded fire-resistant coatings, delays the temperature growth of steel structures, protects steel from fire damage, and extends the fire resistance limit.
Smart Images

Figure CN119264712A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fireproof material application, and in particular relates to an expansion type steel structure fireproof coating and a preparation method thereof. Background Art
[0002] Due to its high strength, good seismic resistance, large spatial span, convenient construction and short construction time, steel structure buildings have gradually developed into the mainstream of modern buildings and are widely used in large-span spatial structures and high-rise buildings.
[0003] Although steel is a non-combustible building material, its mechanical properties (elastic modulus, yield strength and tensile strength, etc.) decrease as the temperature rises under fire or high temperature. When the temperature is higher than 500°C, it will drop sharply and lose its original bearing capacity, causing the steel building to collapse. Generally, the fire resistance limit of unprotected steel structures is about 15 minutes.
[0004] At present, the fire protection methods for steel structures include outer cladding, flushing, shielding and fireproof coating. Among them, spraying fireproof materials on steel structures is a practical, convenient and simple construction method. According to the fire protection principle, steel structure fireproof materials can be divided into two types: non-expansive and expansive. Among them, the expansive fire retardant coating has the characteristics of high construction efficiency, low construction difficulty and small impact on the environment compared with the non-expansive type, so it is widely used. Improving the fire resistance of the expansive fire retardant coating is one of the current ways to improve the expansive fire retardant coating. Summary of the invention
[0005] The present invention aims to improve the fire resistance of the intumescent fire retardant coating and provides an intumescent steel structure fire retardant coating which has a reasonable formula, is simple to prepare and can effectively improve the fire resistance of the intumescent fire retardant coating and a preparation method thereof.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: the present invention provides an intumescent fire retardant coating for steel structures, which comprises the following components in parts by weight:
[0007]
[0008]
[0009] The balance is water, wherein the binder is a mixture of epoxy ester-modified water-based acrylic acid, polyvinyl alcohol, and urea in a mass ratio of 7:1:2, and the filler is a mixture of hydroxylated titanium dioxide composite glass hollow microspheres, porous ceramic powder, and inorganic mineral powder in a mass ratio of 1:1:2.
[0010] Preferably, the carbon-nitrogen-phosphorus expansion system is an expansion system with ammonium polyphosphate as the acid source, pentaerythritol as the carbon source and melamine as the gas source.
[0011] Preferably, the mass ratio of the ammonium polyphosphate, pentaerythritol and melamine is 5:2:3.
[0012] Preferably, the inorganic mineral powder is at least one of montmorillonite powder, basalt powder, mica powder, vermiculite powder and kaolin.
[0013] The present invention also provides a method for preparing the above-mentioned intumescent steel structure fire retardant coating, comprising the following steps:
[0014] a. First, add the titanium dioxide composite hollow glass microspheres into a mixed solution of sodium hydroxide and ethanol, heat and reflux for 12 hours, filter and dry to obtain hydroxylated titanium dioxide composite hollow glass microspheres for standby use;
[0015] b. Then, after dissolving urea in water, add epoxy ester-modified water-based acrylic acid and polyvinyl alcohol in sequence, stir for one hour to obtain the desired binder for standby use;
[0016] c. Then, the carbon-nitrogen-phosphorus expansion system was added to water and ultrasonically treated for 3 hours to obtain a suspension;
[0017] d. Then, add defoamer, film-forming agent, thickener and dispersant to the suspension in sequence and stir in a water bath at 40°C for 1 hour;
[0018] e. After stirring is completed, add the binder to the suspension and continue stirring for 1 hour;
[0019] f. After the stirring is completed, mix the hydroxylated titanium dioxide composite glass hollow microspheres, porous ceramic powder and inorganic mineral powder evenly, add them into the suspension, and stir for 1 hour to obtain the required intumescent steel structure fire retardant coating.
[0020] Compared with the prior art, the advantages and positive effects of the present invention are:
[0021] 1. The intumescent steel structure fire retardant coating provided by the present invention improves the existing binder and filler, utilizes epoxy ester to modify acrylic acid, so that the stability and viscosity of acrylic acid are improved, and at the same time, polyvinyl alcohol is used to further increase the viscosity of acrylic acid, and then the property of urea that decomposes into melamine, ammonia and carbon dioxide when heated is utilized to further supplement the gas source in the carbon-nitrogen-phosphorus expansion system, so that the carbon source is better expanded into a porous structure while increasing the release efficiency of the flame-retardant gas, thereby achieving the purpose of further flame retardancy. At the same time, the titanium dioxide composite glass hollow microspheres themselves have the effect of increasing strength, and the hydroxylated titanium dioxide composite glass hollow microspheres further lose water during the reaction process, so as to better polymerize with the carbon source to form a porous carbonaceous layer with good fire retardant performance, effectively protecting the steel from damage by fire. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 The thermal insulation performance curve of the coating provided in Example 1;
[0024] Figure 2 1.5 μm SEM image provided for Example 1;
[0025] Figure 3 This is the 300nm SEM image provided in Example 1. DETAILED DESCRIPTION
[0026] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0028] Example 1: This example provides a method for preparing an intumescent fire retardant coating for steel structures.
[0029] First, 8 parts of carbon-nitrogen-phosphorus expansion system (4 parts of ammonium polyphosphate, 1.6 parts of pentaerythritol, 2.4 parts of melamine), 3.92 parts of epoxy ester-modified water-based acrylic acid, 0.56 parts of polyvinyl alcohol, 1.12 parts of urea, 0.4 parts of titanium dioxide composite glass hollow microspheres, 0.4 parts of porous ceramic powder, 0.8 parts of montmorillonite powder, 0.1 parts of defoaming agent (CS-300L), 0.5 parts of film-forming agent (RTC-12), 0.1 parts of thickener (TT-935) and 0.1 parts of dispersant (LP-91) were weighed according to their weight ratios.
[0030] The acid source in the carbon-nitrogen-phosphorus expansion system can be replaced by potassium ammonium polyphosphate, melamine phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and other materials. The carbon source can be dipentaerythritol, sucrose, starch, sorbitol and other materials. The gas source can be dicyandiamide, glycine, chlorinated paraffin and other materials. However, considering the consistency of decomposition temperature, ammonium phosphate, pentaerythritol and melamine are preferred. These three materials are also the materials of the existing common flame-retardant expansion system. For this reason, they are not described in this embodiment.
[0031] Considering that the main function of the filler is to improve the antioxidant properties of the carbon layer and enhance the strength of the coating, the addition of titanium dioxide composite glass hollow microspheres itself has these characteristics. At the same time, considering that the main purpose of the carbon-nitrogen-phosphorus expansion reaction is to absorb heat, and as the heat increases, the hydroxylated titanium dioxide composite glass hollow microspheres will dehydrate, and at the same time, it is convenient to fill them into the carbon layer, thereby forming a denser expanded carbon layer. At the same time, the addition of porous ceramic powder is also to fill the filler and the carbon layer with each other, thereby further improving the density. The addition of urea is mainly considered to be related to the formation of pores and gas, and the pyrolysis temperature of urea is about 130°C, and its pyrolysis will form melamine, nitrogen and carbon dioxide, among which melamine itself is a component of the gas source, and nitrogen and carbon dioxide can form flame-retardant gas to dilute oxygen and other combustible gases. In this way, it first pyrolyzes to achieve a certain purpose of endothermic flame retardancy while providing more gas sources, which is conducive to the formation of carbon pores.
[0032] Similarly, the quality of coatings is related to physical and chemical properties such as adhesion, hiding power, hardness, elongation, water resistance, and weather resistance. Epoxy ester-modified water-based acrylics have better stability and adhesion than water-based acrylics. By adding polyvinyl alcohol, their adhesion is even better, thus providing better adhesion.
[0033] During the preparation, the titanium dioxide composite hollow glass microspheres are first added to a mixed solution of sodium hydroxide and ethanol, heated and refluxed for 12 hours, filtered and dried to obtain hydroxylated titanium dioxide composite hollow glass microspheres for later use. Through infrared spectroscopy, it can be found that the hydroxylated titanium dioxide composite hollow glass microspheres have a wavelength of 3300 cm -1 The vibration peak of the OH group at is enhanced, indicating that the hydroxylation is successfully prepared.
[0034] Then, after dissolving urea in water, epoxy ester-modified water-based acrylic acid and polyvinyl alcohol were added in sequence, and stirred for one hour to obtain the required binder for use; then, the carbon-nitrogen-phosphorus expansion system was added to water, and ultrasonically treated for 3 hours to obtain a suspension; then, a defoamer, a film-forming agent, a thickener and a dispersant were added to the suspension in sequence and stirred for one hour in a water bath at 40°C; after the stirring was completed, the binder was added to the suspension and the stirring was continued for 1 hour.
[0035] After the stirring is completed, the hydroxylated titanium dioxide composite glass hollow microspheres, porous ceramic powder and inorganic mineral powder are mixed evenly and added to the suspension, and stirred for 1 hour to obtain the required intumescent steel structure fire retardant coating. It should be noted that water can account for between 26% and 42% of the total mass.
[0036] Performance test: The basic performance of the coating is tested according to the provisions of GB 14907-2018 "Fire Retardant Coatings for Steel Structures".
[0037] Samples: steel plates coated with the coating provided in Example 1, steel plates coated with steel structure fire retardant coating with item number GJG03, and uncoated steel plates, the thickness of the steel plates are consistent.
[0038] The results are as follows Figure 1 As shown in the figure, starting from time 0, the thermal insulation performance of the three samples increased in almost the same trend within 10 minutes, and then the temperature of the back of the uncoated steel plate rose sharply. It was close to 400°C within 60 minutes. The steel plate coated with the steel structure fire retardant coating with the article number GJG03 was close to 300°C within 60 minutes, while the coating provided in this embodiment remained below 300°C within 60 minutes and the temperature increased slowly. At the same time, through Figure 2 and Figure 3 From the SEM image, it can be found that a large number of titanium dioxide composite glass hollow microspheres are filled in the carbon layer, making the entire structure dense.
[0039] Example 2: This example provides a method for preparing an intumescent fire retardant coating for steel structures.
[0040] According to weight proportions, weigh 21 parts of carbon-nitrogen-phosphorus expansion system (10.5 parts of ammonium polyphosphate, 4.2 parts of pentaerythritol, 6.3 parts of melamine), 10.29 parts of epoxy ester-modified water-based acrylic acid, 1.47 parts of polyvinyl alcohol, 2.94 parts of urea, 1.05 parts of titanium dioxide composite glass hollow microspheres, 1.05 parts of porous ceramic powder, 2.1 parts of montmorillonite powder, 0.3 parts of defoamer (CS-300L), 1 part of film-forming agent (RTC-12), 0.5 parts of thickener (TT-935) and 0.3 parts of dispersant (LP-91).
[0041] The preparation method is the same as that in Example 1 and is not described in detail here.
[0042] Example 3: This example provides a method for preparing an intumescent fire retardant coating for steel structures.
[0043] According to weight proportions, weigh 15 parts of carbon-nitrogen-phosphorus expansion system (7.5 parts of ammonium polyphosphate, 3 parts of pentaerythritol, 4.5 parts of melamine), 7.35 parts of epoxy ester-modified water-based acrylic acid, 1.05 parts of polyvinyl alcohol, 2.1 parts of urea, 0.26 parts of titanium dioxide composite glass hollow microspheres, 0.26 parts of porous ceramic powder, 5.2 parts of montmorillonite powder, 0.2 parts of defoamer (CS-300L), 0.7 parts of film-forming agent (RTC-12), 0.3 parts of thickener (TT-935) and 0.2 parts of dispersant (LP-91).
[0044] The preparation method is the same as that in Example 1 and is not described in detail here.
[0045] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. An intumescent fire retardant coating for steel structures, characterized in that: The following ingredients are included in parts by weight: The balance is water, wherein the binder is a mixture of epoxy ester-modified water-based acrylic acid, polyvinyl alcohol, and urea in a mass ratio of 7:1:2, and the filler is a mixture of hydroxylated titanium dioxide composite glass hollow microspheres, porous ceramic powder, and inorganic mineral powder in a mass ratio of 1:1:
2.
2. The intumescent fire retardant coating for steel structures according to claim 1, characterized in that: The carbon-nitrogen-phosphorus expansion system is an expansion system with ammonium polyphosphate as an acid source, pentaerythritol as a carbon source and melamine as a gas source.
3. The intumescent fire retardant coating for steel structure according to claim 2, characterized in that: The mass ratio of the ammonium polyphosphate, pentaerythritol and melamine is 5:2:
3.
4. The intumescent fire retardant coating for steel structures according to claim 1, characterized in that: The inorganic mineral powder is at least one of montmorillonite powder, basalt powder, mica powder, vermiculite powder and kaolin.
5. The method for preparing the intumescent fire retardant coating for steel structure according to any one of claims 1 to 4, characterized in that: The following steps are involved: a. First, add the titanium dioxide composite hollow glass microspheres into a mixed solution of sodium hydroxide and ethanol, heat and reflux for 12 hours, filter and dry to obtain hydroxylated titanium dioxide composite hollow glass microspheres for standby use; b. Then, after dissolving urea in water, epoxy ester-modified water-based acrylic acid and polyvinyl alcohol are added in sequence. Stir for one hour to obtain the desired binder for later use; c. Then, the carbon-nitrogen-phosphorus expansion system was added to water and ultrasonically treated for 3 hours to obtain a suspension; d. Then, add defoamer, film-forming agent, thickener and dispersant to the suspension in sequence and stir in a water bath at 40°C for 1 hour; e. After stirring is completed, add the binder to the suspension and continue stirring for 1 hour; f. After the stirring is completed, mix the hydroxylated titanium dioxide composite glass hollow microspheres, porous ceramic powder and inorganic mineral powder evenly, add them into the suspension, and stir for 1 hour to obtain the required intumescent steel structure fire retardant coating.
Citation Information
Patent Citations
Ultrathin water-based epoxy resin expandable fireproof paint and preparation method thereof
CN101712840A
Steel-structure ultrathin intumescent fire retardant coating and preparation method thereof
CN101747821A
High-stability water-based paint suitable for various substrates and preparation method thereof
CN113462248A
Methods for forming and uses of titania-coated inorganic particles
US20220089881A1